Incidence rate of Healthcare Associated Infections in a COVID-19 Intensive Care Unit. (20th October 2021) - Marte, M; Marotta, D; Giannini, D; Mazzalai, E; Barone, LC; Baccolini, V; Migliara, G; Marzuillo, C; De Giusti, M; Villari, P
Abstract: Background: Intensive Care Units (ICU) faced a high pressure under the COVID-19 pandemic. It is recognized that patients admitted in these wards are more susceptible to Healthcare Associated Infections (HAIs). This study aims at comparing the incidence of HAIs in a COVID-19 ICU to a No-COVID ward. Methods: A retrospective cohort study including patients admitted to the ICU of the Teaching Hospital Policlinico Umberto I in Rome from April 2020 to March 2021 was performed. Data on age, gender, hospitalization, different types of devices (ventilation, central venous and urinary catheter), number and type of device-related HAI were collected. Statistical analyses were performed with Episheet and STATA 13. Results: Out of 347 patients admitted in the ICUs, 329 were included in the study (217 had COVID-19 and 112 had not). In the COVID-19 group, patients were mainly male (69.58%) with a mean age of 62.5±13.5 years, whereas the other group was slightly older (63.2±16.2 years) and more balanced between the two sexes (52.68% male). A total of 133 patients developed at least one HAI, 94 of which were SARS-CoV-2 positive. Globally, 246 HAIs were diagnosed: 163 occurred in the COVID group and 83 in the No-COVID one. The cumulative days of hospitalization were 3233 for the COVID group and 2134 for the No-COVID. The incidence of HAI considered for 1000 days of hospitalization among COVID patients was 50.42 (IC 95%: 42.97-58.78), compared to 38.89 (IC 95%: 30.98-48.22) for the No-COVID one, for an incidence rate ratio of 1.30 (IC 95%: 0.99-1.71). Conclusions: Even though the confidence interval contains the value 1, the results point out that there is an increase in the incidence rate of HAI among COVID-19 patients. Further investigations are needed to better understand the reasons behind the present findings. Key messages: Patients admitted to Intensive Care Units are more susceptible to Healthcare Associated Infections. Our study aims at describing the impact of COVID-19 on the risk of developing such conditions. Being infected with COVID-19 leads to an increase in the incidence rate of Healthcare Associated Infections. Further studies are needed to understand the underlying reasons.